2014
DOI: 10.1002/chem.201404922
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Polypyridyl and Cyclometalated Ruthenium(II) Complexes: Anticancer Activities Against 2D and 3D Cancer Models

Abstract: The aim of this study was to illustrate the dramatically different anticancer activities between coordinatively saturated polypyridyl (1 a-4 a) and cyclometalated (1 b-4 b) ruthenium(II) complexes. The cyclometalated complexes 1 b-4 b function as DNA transcription inhibitors, exhibiting switch-on cytotoxicity against a 2D cancer cell monolayer, whereas the polypyridyl complexes 1 a-4 a are relatively inactive. Moreover, complexes 1 b-4 b exhibit excellent cytotoxicity against 3D multicellular tumor spheroids (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 63 publications
8
73
0
Order By: Relevance
“…This result is in line with the anticancer activity reported for some structurally similar Ru II complexes. [24,[64][65][66][67] The Ir III complex 2 showed, as a general trend, a higher cytotoxic activity in the dark on all cell lines than 1 (see Table S1). We can speculate that the planar, highly conjugated L2 ligand plays a role in the dark cytotoxicity of 2.…”
Section: Dark Toxicity and Phototoxicitymentioning
confidence: 86%
“…This result is in line with the anticancer activity reported for some structurally similar Ru II complexes. [24,[64][65][66][67] The Ir III complex 2 showed, as a general trend, a higher cytotoxic activity in the dark on all cell lines than 1 (see Table S1). We can speculate that the planar, highly conjugated L2 ligand plays a role in the dark cytotoxicity of 2.…”
Section: Dark Toxicity and Phototoxicitymentioning
confidence: 86%
“…Based on the previous reports, Ru complexes act by intercalating with DNA in nucleus to inhibit DNA replication and transcription [3]. Therefore, delivery of Ru complexes to cell nucleus would be an ideal method to enhance their anticancer efficacy.…”
Section: Translocation and Triggered Drug Release Of Bio-cage@ru In Nmentioning
confidence: 99%
“…So far, the synthesized Ru complexes such as NAMI-A and KP1019 have gone through phase I clinical trials. Despite this partial success, the new class of Ru-based chemotherapeutics is still associated with drawbacks such as unstability in aqueous solution, unsatisfied cytotoxicity and uncertained antitumoral mechanism for the cancer therapy [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the MLCT emission strongly depends on the orbital combination of polypyridyl ligands, the emission properties could be readily modulated by the variation of ligand properties [9,12,17,31,32], which provides a useful approach for the development of polypyridyl-ruthenium(II) complex-based luminescent chemosensors [33e39]. In previous works, we identified that the MLCT excited state of ruthenium(II) complexes could be corrupted by the intramolecular photoinduced electron transfer (PET) process when an electron donor or acceptor was attached to polypyridyl ligands, and the elimination of PET by the analyte-triggered reaction could restore the MLCT state to switch on the luminescence of the complexes [40e42].…”
Section: Introductionmentioning
confidence: 99%